An Analysis of the Constitutionality of Bail Pending Appeal in Light of the Supreme Court Decision in the Case of Arvind Patel Versus Uganda - Regan Taremwa (Uganda Christian University, 2024)
Article 23(6) of the Constitution of Uganda 1995, as Amended provides that an arrested person is entitled to apply to court for bail. However, it is silent on the issue of bail pending appeal. Bail pending appeal is provided for in the Magistrates Courts Act, the Judicature Act and the Criminal Procedure Code Act. Although the Supreme Court in Arvind Patel vs Uganda SCCA No.1 of 2003, provided criteria for the granting bail pending appeal, some high court and Court of Appeal judges, who are bound by the decisions of the Supreme Court, have ignored these criteria. There are conflicting Court of Appeal and Supreme Court judgements on the question of whether Article 23(6) is applicable to bail pending appeal and whether the right to be presumed innocent is applicable to a person who is applying for bail pending appeal. There are notable controversies in the rich jurisprudence of the Supreme Court on bail pending appeal as set in Arvind Patel vs Uganda. Take for instance, In October 2020, one of the justices of the Supreme Court held that the Supreme Court does not have jurisdiction to grant bail pending appeal and that Rule 6(2)(a), which empowers the Supreme Court to grant bail pending appeal, is unconstitutional thus noted that the decision in Arvind Patel vs Uganda was wrongly decided. In November 2020, another Supreme Court justice granted an applicant bail pending appeal affirming the decision in Arvind Patel vs Uganda. This paper seeks to examine the jurisprudence developed by the courts of Uganda on the grant of bail pending appeal with a look at Arvind Patel vs Uganda by focusing on the courts with jurisdiction to grant bail pending appeal; the right to bail pending appeal; the presumption of innocence and bail pending appeal; and conditions for granting bail pending appeal.